2023
DOI: 10.7717/peerj.16202
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 facilitates heart failure progression through regulating TGF-β-induced cardiac remodeling

Peng Qi,
Qian Zhai,
Xiquan Zhang

Abstract: Background Heart failure is caused by acute or chronic cardiovascular diseases with limited treatments and unclear pathogenesis. Therefore, it is urgent to explore new therapeutic targets and reveal new pathogenesis for heart failure. Methods We carried out heart failure animal model by transverse aortic arch constriction (TAC) in mice. The left ventricular internal diameter diastole (LVIDd), left ventricular internal diameter systole (LVIDs), and ejection fraction (EF) value were detected using ultrasound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“… [ 129 ] Apoptosis in HF is predominantly driven by factors like oxidants, excessive nitric oxide, angiotensin II, and catecholamines, which trigger caspase activation leading to cardiomyocyte death, a key aspect in the progression of HF. [ 130 ] necroptosis The study found that RIPK1-independent necroptosis contributes to the pathogenesis of DIC, and treatment with rapamycin significantly improves heart function in DIC by reducing MLKL activity and preventing necroptosis. [ 131 ] This paper discusses the mechanisms of cell death, including apoptosis, necrosis, and autophagy.…”
Section: Panoptosome In Heart Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 129 ] Apoptosis in HF is predominantly driven by factors like oxidants, excessive nitric oxide, angiotensin II, and catecholamines, which trigger caspase activation leading to cardiomyocyte death, a key aspect in the progression of HF. [ 130 ] necroptosis The study found that RIPK1-independent necroptosis contributes to the pathogenesis of DIC, and treatment with rapamycin significantly improves heart function in DIC by reducing MLKL activity and preventing necroptosis. [ 131 ] This paper discusses the mechanisms of cell death, including apoptosis, necrosis, and autophagy.…”
Section: Panoptosome In Heart Diseasesmentioning
confidence: 99%
“…The heart’s response to damage and stress is known as cardiac remodeling, and it involves structural alterations, myocardial cell enlargement, and an increase in apoptosis. The remodeling process is intimately associated with the advancement of HF, as the heart’s capacity to contract efficiently and sustain sufficient blood circulation is compromised by the death of cardiomyocytes [ 130 ]. According to recent studies, HF symptoms and cell preservation may benefit from caspase inhibitor-induced apoptosis inhibition, both in vivo and in vitro.…”
Section: Panoptosome In Heart Diseasesmentioning
confidence: 99%